Entre a negritude e a africanidade: construção da identidade negra em Mato Grosso - Batista, Michelangelo Henrique (Universidade do Vale do Rio dos Sinos, 2011)
Assuming that all black is a human architect, this research seeks to demonstrate the possibility of individual black identities - multiple notions of blackness. The situation in color and architectural behavior of the individual to take it a different view, contemporary black identity, which gives individual identity, does not refute the black collective. With own meanings theoretical and based on authors such as Guimarães (2003), Honneth (2003), Nogueira (1985), Simmel (1977), among others, spoke about the real existence of intense and Ideology of African and multiple notions of blackness, taking into account the performance brand of prejudice. The incursion of thumb developed in a qualitative way, held in two cities in Mato Grosso, used as a form of participant observation research, combined with other research techniques. The theoretical and empirical trajectory allowed us to obtain favorable results on the existence of different definitions of blackness, which does not simplify the existence of black a human architect.
Keywords: Identidade; Indivíduo negro; Ideologia de africanidade; Múltiplas noções de negritude; Identity; Blacks; Black, a human architect; Ideology of africans; Multiple notions of blackness; Negro, ser arquiteto; ACCNPQ::Ciências Humanas::Sociologia